How Much Do Test Scores Vary Among School Districts? New Estimates Using Population Data, 2009–2015. (May 2018) - Fahle, Erin M.; Reardon, Sean F.
This paper provides the first population-based evidence on how much standardized test scores vary among public school districts within each state and how segregation explains that variation. Using estimates based on roughly 300 million test score records in math and English Language Arts (ELA) for Grades 3 through 8 from every U.S. public school district during the 2008–09 to 2014–15 school years, we estimate intraclass correlations (ICCs) as a measure of between-district variation. We characterize the variation in the ICCs across states as well as the patterns in the ICCs over subjects, grades, and cohorts. Further, we investigate the relationship between the ICCs and measures of racial and socioeconomic segregation. We find that between-district variation is greatest, on average, in states with high levels of both White-Black and economic segregation.